KETERPADUAN BLOK TUNJUNGAN DALAM KONTEKS PERENCANAAN KOTA YANG IDEAL - Redyantanu, Bramasta Putra (RUAS, 2017)
The good city is an indication of good process of urban planning. In the planning phase, there is a simulation process about how all kinds of urban elements are related, and also have good synergistic between one another. Tunjungan, as one of the city blocks that formed the image of Surabaya, is an example of dynamic development. The big gap between ideal arrangement and real conditions can not be avoided. Partial development of it is one of the reason. This study is the identification of the gap between good city condition that expected by the planners, against the real condition in the field. The result will show which urban elements are lacking, but potentially can be fixed. The final findings are some guidance to develop Tunjungan block more synergy with the purpose of initial planning.